2013
DOI: 10.1111/cyt.12071
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a cytopathologist increases the diagnostic accuracy of endoscopic ultrasound‐guided fine needle aspiration cytology for pancreatic adenocarcinoma: a meta‐analysis

Abstract: Objective A meta-analysis has not been previously performed to evaluate critically the diagnostic accuracy of endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) of solely pancreatic ductal adenocarcinoma and address factors that have an impact on variability of accuracy. The aim of this study was to determine whether the presence of a cytopathologist, variability of the reference standard and other sources of heterogeneity significantly impacts diagnostic accuracy. Methods We conducted a comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
232
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(242 citation statements)
references
References 39 publications
2
232
0
8
Order By: Relevance
“…The largest published meta-analyses of EUS-FNA in solid pancreatic lesions showed sensitivity and specificity values of 83-92 % and 94-100 %, respectively [10,12,27,28], although the false-negative rate of EUS-FNA can reach as high as 12 % [28][29][30][31][32][33]. Moreover, a randomized controlled trial by Horwhat et al [3] comparing EUS-FNA to CT-/ US-FNA revealed no significant differences between the endoscopic and percutaneous approaches for the diagnosis of malignant pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest published meta-analyses of EUS-FNA in solid pancreatic lesions showed sensitivity and specificity values of 83-92 % and 94-100 %, respectively [10,12,27,28], although the false-negative rate of EUS-FNA can reach as high as 12 % [28][29][30][31][32][33]. Moreover, a randomized controlled trial by Horwhat et al [3] comparing EUS-FNA to CT-/ US-FNA revealed no significant differences between the endoscopic and percutaneous approaches for the diagnosis of malignant pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The many published papers dealing with pancreatic FNA have shown a variable rate of inadequate samples[1,2,12,13], which surpassed 15 % for the percutaneous approach…”
mentioning
confidence: 99%
“…Despite numerous studies addressing these issues, many endoscopists are still perplexed about the nature of the best practices needed to ensure optimal results, in particular with regard to the need for on-site cytopathology for skilled and experienced endosonographers practicing at a high-volume center. To date, multiple meta-analyses have confirmed the diagnostic accuracy, cost-effectiveness, accuracy, and safety of EUS-FNA for solid pancreatic lesions [8][9][10][11][12]. Moreover, structured literature reviews have concluded that rapid on-site evaluation (ROSE) improves diagnostic accuracy [8,9].…”
mentioning
confidence: 96%
“…Vários estudos relatam que o ROSE, permitindo avaliar a presença ou não do material adequado 104 , aumenta a acurácia, além de diminuir o número de punções necessárias 102,103 . Em revisão sistemática e metanálise 104 , incluindo 34 estudos e mais de 3600 pacientes, foi comprovada a superioridade do ROSE em relação à EE-PAAF sem presença do citologista em sala.…”
Section: Complicaçõesunclassified
“…Em revisão sistemática e metanálise 104 , incluindo 34 estudos e mais de 3600 pacientes, foi comprovada a superioridade do ROSE em relação à EE-PAAF sem presença do citologista em sala.…”
Section: Complicaçõesunclassified